Feeding Mode of Australian Infants in the First 12 Months of Life: An Assessment against National Breastfeeding Indicators - Magarey, A.; Kavian, F.; Scott, Jane; Markow, K.; Daniels, L. (2015)
BACKGROUND: In 2011, Australia published a set of 6 population-level indicators assessing breastfeeding, formula use, and the introduction of soft/semisolid/solid foods. OBJECTIVES: This study aimed to report the feeding practices of Australian infants against these indicators and determine the predictors of early breastfeeding cessation and introduction of solids. METHODS: Mother-infant dyads (N = 1470) were recruited postnatally in 2 Australian capital cities and regional areas of 1 state between February 2008 and March 2009. Demographic and feeding intention data were collected by self-completed questionnaire at infant birth, with feeding practices (current feeding mode, age of breastfeeding cessation, age of formula and/or solids introduction) reported when the infant was between 4 and 7 months of age, and around 13 months of age. Multiple logistic regression was used to determine the predictors of breastfeeding cessation and solids introduction. RESULTS: Although initiation of breastfeeding was almost universal (93.3%), less than half of the infants were breastfed to 6 months (41.7%) and 33.3% were receiving solids by 4 months. Women who were socially disadvantaged, younger, less educated, unpartnered, primiparous, and/or overweight were most likely to have ceased breastfeeding before 6 months of age, and younger and/or less educated women were most likely to have introduced solid food by 4 months of age. Not producing adequate milk was the most common reason provided for cessation of breastfeeding. CONCLUSION: The feeding behaviors of Australian infants in the first 12 months fall well short of recommendations. Women need anticipatory guidance as to the indicators of breastfeeding success and the tendency of women to doubt the adequacy of their breast milk supply warrants further investigation.